Pemanfaatan Limbah Ampas Tahu Dalam Upaya Diversifikasi Pangan - Maysura MD; Khairunnisa Rangkuti; Misril Fuadi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2019)
Tofu pulp is a by-product of tofu processing which still contains high enough protein because in the process of knowing not all proteins can be extracted. The focus of the problem on the local community starts from observations in the field where some people have a home industry that knows its pulp not yet maximally utilized only limited to animal feed additives. Based on this problem it is necessary to empower rural communities, especially household mother by providing counseling and training on the use of vilages such as tofu industry waste to be processed into useful products with high economic value.Tofu dregs become crackers and abon in addition to nutritious family food (food diversification) as well as additional household income